Identification of a novel RMST-ALK rearrangement in advanced lung adenocarcinoma and durable response to ceritinib: A case report - Li, Hui; Deng, Yixiao; Chen, Bin; Xiao, Yajie; Yang, Jie; Liu, Qionghui; Lin, Gengpeng (Frontiers in Oncology, 2022)
As next-generation sequencing technology has enabled clinicians to identify 5' partners and 3' kinases involved in anaplastic lymphoma kinase (ALK) fusions in clinical practice, various ALK fusion partners have been confirmed in non-small cell lung cancer (NSCLC). Here, a novel rhabdomyosarcoma 2 associated transcript (RMST)-ALK rearrangement was identified in an 80-year-old Chinese male with advanced lung adenocarcinoma. Therefore, he was initialed with certinib treatment, and a remarkable partial response lasted for at least 14 months. Our findings may provide additional evidence for ceritinib treatments in NSCLC patients with the ALK rearrangement.